Preliminary study on the synthesis of kojic acid monooleate using dual enzymes system - Radzi S.M.; Zulhilmi M.N.M.; Noor H.M.; Rehan M.M. (American Institute of Physics Inc., 2024)
Kojic acid is an organic acid that widely used in cosmetic, health care, food and chemical industries. However, kojic acid is not stable at high temperature, for long storage and it has low lipophilic properties. To overcome this problem, a study was conducted to improve its properties by enzymatic reaction. This study was focused on the synthesis of kojic acid monooleate from kojic acid and oleic acid using enzymatic catalysts at optimized conditions. This study was divided into three parts starting from enzymatic synthesis of kojic ester or specifically kojic acid monooleate (KAMO) by using a dual enzymes system that consisted of Novozym 435 and Lipozyme RM IM. Then, optimization of four variables such as screening of dual enzymes ratio, temperature, substrate molar ratio and the reaction time via conventional method of one parameter at-a-time approach and lastly verification of the product using Fourier Transfer Infrared (FTIR) spectroscopy. The optimum conditions for the enzymatic synthesis of KAMO were at the dual enzymes ratio (1:1) of Novozym 435 and Lipozyme RMIM, temperature at 50C, the molar ratio of kojic acid and oleic acid were 4:1 respectively and 24 hours of reaction time. The highest percentage conversion of KAMO achieved at the most optimum conditions was 13.22 %. Finally, kojic ester produced was verified by using FTIR proved the presence of ester bond (C=O) at 1743 cm-1. 2018 Author(s).